PENGEMBANGAN SISTEM HOT WIRE UNTUK PENUMBUHAN LAPISAN TIPIS SILIKON POLIKRISTAL DENGAN KONDUKTIVITAS TINGGI - P. Simanjuntak, Mariati
Abstract: It has been grown polycrystalline silicon thin film on silicon wafer <111>, using Hot Wire Plasma Enhanced Chemical Vapor Deposition (HW-PECVD). Silane gas (SiH4), 10% diluted in H2 was used as a gas source. Deposition rate varied from 8.95 Å/s to 14.57 Å/s for substrate temperatur 175°C to 275°C at filament temperature about 1000°C and 70 sccm flow rate of silane. XRD characterization showed peaks at crystal orientation <111>, <220>, and <311>. SEM characterization showed polycrystalline appearance with grain size between 373 Å to 682 Å at crystal orientation <111>. Dark conductivity of polycrystalline silicon obtained is from 1.38x10-5 S/cm to 1.97x10-4 S/cm. This high value is good enough for application as active layer in TFT.